Evaluation of immunomodulatory effects of lomefloxacin in mice - Arfa Majeed; Aqeel Javeed; Muhammad Ovais Omer; Muhammad Hassan Mushtaq; Adeel Sattar (Universidade de São Paulo, 2021)
Lomefloxacin is a flouroquinolone antibiotic that is quite efficacious against many gram negative and gram positive pathogens. Lomefloxacin evince antibacterial effects by modifying DNA gyrase in gram negative pathogens and topoisomerase IV in gram positive pathogens. This study is designed to assess the immunomodulatory effects of lomefloxacin in male albino mice. Three doses of lomefloxacin 12.5 mg/kg, 25 mg/kg and 50 mg/kg were used and delayed type hypersensitivity assay, cyclophosphamide induced neutropenic assay, carbon clearance assay, heamagglutination assay and mice lethality test were performed to evaluate the effects of lomefloxacin on immune system of mice. DTH assay has depicted the significant immunosuppressant potential of lomefloxacin at 25 mg/kg and 50 mg/kg dose. Total leukocyte count have exhibited highly significant reduction (P<0.001) in leukocyte count after cyclophosphamide administration. Differential leukocyte count has shown significant (P<0.01) reduction in lymphocyte count, whereas, highly significant (P<0.001) increase in monocyte count and significant (P<0.05) increase neutrophil count has been observed. In carbon clearance assay, highly significant (P<0.01) increase in phagocytic index has been noted at 12.5 mg/kg and 25 mg/kg doses. Humoral immune system responses are suppressed in dose dependent manner by both heamagglutination assay (P<0.001) and mice lethality assay (P<0.001). Results clearly depict that lomefloxacin possess quite significant immunomodulatory potential.